-2x + 2y + 3z = 0 → 2x - 2y - 3z = 0 → 2x - 2y - 3z = 0
-2x - 1y + 1z = -3 → 2x + 1y - 1z = 3 → 2x + 1y - 1z = 3
2x + 3y + 3z = 5 → 2x + 3y + 3z = 5 -3y - 2z = -3
-2x + 2y + 3z = 0 → 2x - 2y - 3z = 0
-2x - 1y + 1z = -3 → 2x + 1y - 1z = 3 → 2x + 1y - 1z = 3
2x + 3y + 3z = 5 → 2x + 3y + 3z = 5 → 2x + 3y + 3z = 5
-2y - 4z = -2
-3y - 2z = -3 → -6y - 4z = -6
-2y - 4z = -2 → -2y - 4z = -2
-4y = -4
-4 -4
y = 1
-3y - 2z = -3
-3(1) - 2z = -3
-3 - 2z = -3
+ 3 + 3
-2z = 0
-2 -2
z = 0
-2x + 2y + 3z = 0
-2x + 2(1) + 3(0) = 0
-2x + 2 + 0 = 0
-2x + 2 = 0
- 2 - 2
-2x = -2
-2 -2
x = 1
(x, y, z) = (1, 1, 0)
Answer:
maximum
vertex at (-1,1)
axis of symm: x = -1
2 solutions
(-2,0) and (0,0)
Step-by-step explanation:
90 = 20 + 70.....GCF of 20 and 70 is 10
90 = 10(2 + 7) <==
can u write another expression using a different common factor...yes
90 = 20 + 70.....common factor is 5
90 = 5(4 + 14) <==
We need to have some choices to give you the answer